Status of Foreign Labour Migration and Impact of Migrants by COVID-19 in Nepal - Mishra, Manamaya (Patan Prospective Journal, 2022)
The paper based on the status of labour migration and remittances of Nepal in 2014 to 2022. The aims of this paper are to find out the situation of foreign labour migration in Nepal and to examine the impact of COVID[1]19 on the Outflow of Nepali Migrants. It is descriptive in nature and entirely based on secondary sources of information. The trends in foreign employment are presented for past eight years, 2009/10-2018/19. Although Nepal labour migration report 2022 and prelimanari report of 2021, this report reiterates those trends along with updated data from the past fiscal year to create a single comprehensive report. According to National Living Standard Survey 2011, 56 percent of Nepali households have at least one member of their family working and living abroad. The remittances sent by these members have helped improve the standard of living of Nepali households. In 2020, the remittances sent by migrant workers covered to 23.5 percent of the Nepal’s Gross Domestic Product (GDP). Therefore, international labor migration plays a huge role in keeping Nepal’s economy afloat. The decision of the youths to go abroad as labor was a strategy to escape from the potential threat, livelihood options, and get new country experience which ultimately became the major source to bring back remittance. Though low- skilled, foreign labor migration has been the major phenomenon for the country, which is now fully dependent on the remittance economy and counts for over one- fourth of the total national income. Nepal has undertaken several policy measures to overcome these anomalies. Although the implementation aspect is fragile to meet the ground reality, and from the notion of strategic intervention, it is necessary to revisit the policy measures to make foreign labor migration safe, secure, and informed choice based.